Ctrl + Alt + Repeat: Strategies for Regaining Authority Control after a Migration. Issue 1 (19th May 2021) - Carlstone, Jamie
ABSTRACT: In 2019, a new position of Authority Metadata Librarian was created at Northwestern University Libraries. Authority work is an important process that allows for the disambiguation of subjects and names in order to provide consistent, accurate access points in our discovery systems. The Authority Metadata Librarian was charged with setting ongoing authority control workflows and cleaning up the backlog of problems that had accumulated in the four years since migrating to the Alma library services platform (LSP). While still contributing records to the Library of Congress Name Authority Cooperative Program (NACO), Northwestern had not implemented local authority control workflows in Alma since the migration. This presentation offers a review of the strategic approach the Libraries employed for reinstituting authority control processes in its catalog: first, creating a process for ongoing workflows to realistically maintain authority control when new records are added to the collection and second, dealing with a backlog of problems from years without authority control processes in place. The presentation began with an assessment of the catalog's authority control environment. It included approaches to performing authority control, using tools such as Alma Analytics, Python, and MarcEdit. It also covered some authorities projects done while working from home during the COVID-19 pandemic.